Message - Yusuf, Felix Sunday (Universal Journal of Pharmaceutical Research, 2023)
It’s with pleasure and a sense of fulfillment that I write to congratulate everyone on the successful released our current issue (Volume 8, Issue 5,) of Universal Journal of Pharmaceutical Research. More than ever before, there has been a time when the world is dire need of science—to combat every day health uncertainties than now. This is why our contributions and contributions from published authors in these issues are highly appreciated. Given the high quality of our journal, I am glad to announce that my acquaintance have promised to publish with us on our next issue. It would be very imperative if we take this success stories to our schools and labs to encourage more contributions from colleagues. It is a great sense of fulfillment that we have provided the medium for scientists in medical and pharmaceutical research fields to share their findings and knowledge with the world, to find the lasting remedy to our every day global health challenges. Despite the fact that we have achieved so much, there is still room to do more in order to stay up to speed with the dynamic challenges we face. In a fast-changing world, continuum and improvement in critical aspects of life, is true sustainability. We are glad to announce that this current issue incorporates authors from three continents: Europe, South Asia, Middle East and Africa. We appreciate all those that have worked tirelessly behind the scenes to review and approve contributions from all authors and certify them for publication. As we pray and hope for a more safe, progressive, peaceful and sustainable world. Let’s remember that we can do our bits within our neighborhood to help the world achieve its global goals. Thank you very much.